Micro-CT evaluation of microleakage under orthodontic ceramic brackets bonded with different bonding techniques and adhesives - Ozturk, Firat; Ersoz, Mustafa; Ozturk, Seyit Ahmet; Hatunoglu, Erdem; Malkoc, Siddik (Oxford Univ Press, 2016)
The aim of this study was to evaluate microleakage under orthodontic ceramic brackets bonded with direct and different indirect bonding techniques and adhesives using micro-computed tomography. A total of 30 human maxillary premolars were randomly separated into five groups with six teeth in each group. In group I, teeth were bonded directly with Transbond XT (3M Unitek). In group II, group III, group IV, and group V, teeth were bonded through an indirect technique with Custom I.Q. (Reliance Orthodontic Products), Sondhi Rapid-Set (3M Unitek), RMbond (RMO), and Transbond IDB (3M Unitek), respectively, following the manufacturer's instructions. Micro-CT system model 1172 of Skyscan (Kontich, Belgium) was used to scan all samples. NRecon (Skyscan) version 1.6, CT-Analyser V.1.11 (Skyscan), and TView (SkyScan, Bvba) software programs were used for microleakage evaluation. Microleakage values between the test groups were assessed using the Kruskal-Wallis test, while the Wilcoxon signed rank test was used for within-group comparisons. The level of significance was set at P < 0.05. According to the Kruskal-Wallis analysis of variance test, there were no significant differences among the tested groups, with regard to volume and percentage (microleakage/region of interest x 100) of microleakage values (P < 0.05). The Wilcoxon signed rank test showed that coronal microleakage volume and percentage values significantly differed for RMbond and Transbond IDB groups. In the study, only ceramic brackets were used and microleakage into mini gaps did not show up on the micro-CT image because 50% silver nitrate solution could not penetrate into mini gaps which are smaller than silver nitrate particles. Use of direct and indirect bonding techniques with different adhesives did not significantly affect the amount of microleakage.
Keywords: Metal Brackets; Computed Tomography; Marginal Leakage; Strength; Light; Restorations; Placement; Composite; Systems; Bovine